2014
DOI: 10.3402/tellusa.v66.24041
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the impact of Baltic Sea upwelling on the atmospheric boundary layer

Abstract: A B S T R A C T Coastal upwelling, with a strong sea-surface temperature (SST) signal, is extremely common in the Baltic Sea during the summer months. Although the spatial scale of upwelling is small, its high frequency of occurrence in the semi-enclosed basin may allow the SST signature to have significant feedback onto the lower atmosphere. In this paper, we develop a method to remove the signature of upwelling from SST fields, and use these modified SST fields as the lower boundary condition of an atmospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Coastal upwelling (CU), a phenomenon found in large stratified lakes, estuaries, and oceans [1], is an important process for ecologically sensitive regions of the global ocean, such as the Baltic Sea, a large brackish water body that has a very limited water exchange with the open ocean through the narrow and shallow Danish straits [2]. Its extensive coastlines oriented in many directions also mean that coastal upwelling can occur with sustained wind over the Baltic Sea in almost any direction [3], which makes upwelling quite a common process [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coastal upwelling (CU), a phenomenon found in large stratified lakes, estuaries, and oceans [1], is an important process for ecologically sensitive regions of the global ocean, such as the Baltic Sea, a large brackish water body that has a very limited water exchange with the open ocean through the narrow and shallow Danish straits [2]. Its extensive coastlines oriented in many directions also mean that coastal upwelling can occur with sustained wind over the Baltic Sea in almost any direction [3], which makes upwelling quite a common process [4].…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the satellite optical data shows a clear decline in the chlorophyll-a concentration in the coastal zone and in the shallow Curonian Lagoon, where it drops down by an order of magnitude. It was also shown that a cold upwelling front alters the stratification in the atmospheric boundary layer, leading to a sudden drop of air temperature and near-surface winds.upwelling fronts also importantly modifies the vertical stratification and turbulent regime in the marine-atmosphere boundary layer (MABL), resulting in a change in the surface wind stress and direction in the coastal zone [3,9].Nutrient-rich waters brought up from deeper layers to the surface, particularly in the summer time, and the exposure of upwelled phytoplankton to surface radiation enhances the primary production and phytoplankton biomass during upwelling events [10,11], hence influencing the coastal pelagic communities and higher trophic levels [12]. Moreover, upwelling-related coastal ocean dynamics may eventually modify the spatial patterns of background algae blooms in the coastal zone by transporting them farther offshore.During the summer-time holiday season, CU might also have a negative impact on particular tourist areas as a result of a rapid drop in water and air temperatures near the shore [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Omstedt et al, 2004;Hjalmarsson et al, 2008;Backer and Leppänen, 2008;Wesslander, 2011) and monitored. It is characterized by an important upwelling variability (Norman et al, 2013a;Myrberg and Andrejev, 2003;Lehmann and Myrberg, 2008;Sproson and Sahlée, 2014) and by important river runoffs (Bergstrom, 1994), which were estimated at 17241.9 m 3 s −1 in 2015 (Johansson, 2017). Siegel and Gerth (2012) show that in the Baltic Sea decomposition of organic matter and biological production control the biogeochemical processes.…”
Section: G Parard Et Al: Air-sea Co 2 Fluxesmentioning
confidence: 99%
“…The data were interpolated with the inpainting method [29] [30] in order to visualize the spatial distribution of concentrations and water age. The inpainting method has been used for example for filling data gaps concerning upwelling in the Baltic Sea [31] and the land-atmosphere exchange of carbon, water, and energy in the Northern Chihuahua Desert [32]. Contour maps were drawn of the interpolated descriptive statistics in Matlab.…”
Section: Methodsmentioning
confidence: 99%